Quality characteristics of the selected variant of Paulownia tomentosa (Robust4) wood cultivated in Hungary - Komán, Szabolcs (Maderas. Ciencia y Tecnología, 2022)
Besides the continuously increasing demand for wood, the significant increase in its price also contributes to the increasingly broader use of fast-growing wood species and cultivars. Newer variants are continue to be cross-bred as a result. In case of a new variant within a species, it is questionable how it would adapt to a particular climatic environment and the quality of wood it would yield. The characteristics of the Paulownia tomentosa (Robust4) wood obtained from Hungarian plantations of are generally identical to those of the Paulownia tomentosa. The value of the air dry density - as typically for paulownia species- are very low i.e. 273 kg/m3. Its strength values (compressive strength: 9,6 MPa; tensile strength: 39,3 MPa; bending strength: 41,7 MPa; modulus of elasticity: 4116 MPa; impact bending strength: 1,4 J/cm2) also reach, and in some cases, exceed those of the Paulownia tomentosa (Thunb.) Steud. and the Paulownia Clone in vitro 112 variant. Based on these, we can expect the same wood quality from the Robust4 version as from the other paulownia variants.